THE MAIN TRENDS OF VIETNAM - JAPAN COOPERATION WITHIN THE FRAMEWORK OF BILATERAL STRATEGIC PARTNERSHIP - Євген ПРИПІК (Cхід, 2021)
The article examines the process of formation and development of the comprehensive political and trade and economic cooperation between Japan and the Socialist Republic of Vietnam since 1973, when diplomatic relations were established between the two countries, and then received a new impetus after Vietnam started the market reforms in 1986 and commenced the renewal policy (in Vietnamese – “Đổi Mới”). In 2009, Japan and Vietnam decided to raise the bilateral relations to the level of strategic partnership for the common interests of both countries. In 2010, as part of the official visit of the Prime Minister of Japan to Vietnam, a Joint Declaration on strategic cooperation for peace and prosperity in Asia was adopted. The article focuses on cooperation between the two countries in the framework of international and regional organizations, in particular in the framework of the Trans-Pacific Partnership Agreement, as well as in the framework of the Regional Comprehensive Economic Partnership, in which Japan and ASEAN member states participate. In recent decades Japan has been one of Vietnam’s main foreign economic partners and the second largest investor into Vietnamese economy. At the same time, Japan is the largest sponsor of Vietnam through the Official development assistance program (ODA), actively assisting Vietnam in implementing its national strategy of industrialization and modernization under the framework agreement on cooperation between Vietnam and Japan until 2020 with the prospect of 2030. Besides, the article discusses and analyzes the largest joint projects implemented in Vietnam with the technical and financial assistance from Japan.